Developing Interactive Learning Worksheets (LKPD) with Google Slides for Elementary School Teachers - Ningsih, Endah Rahayu; Mawardi, Mawardi; Dwikurnaningsih, Yari (Jurnal Paedagogy, 2025)
This study aims to develop a training module that equips elementary school teachers with the skills to create interactive Learning Worksheets (LKPDs) using Google Slides, aligning with the demands of 21st-century education. A Research and Development method, following the Borg and Gall model, was employed. The research process involved seven stages: 1) a comprehensive needs assessment and literature review, 2) detailed research planning, 3) development of an initial module draft, 4) small-scale field testing to gather feedback, 5) revision of the module based on initial findings, 6) large-scale field testing to evaluate the module's effectiveness, and 7) final revisions based on the overall results. This study focused on 18 elementary school teachers at SD Kristen 04 Eben Haezer Salatiga. Data was collected through interviews and questionnaires. Qualitative and quantitative analyses were employed to examine the data. The findings revealed that the Google Slides-based LKPD training module was successfully implemented and significantly enhanced teachers' pedagogical competencies in designing interactive learning materials using this digital tool. The validity of the training module was confirmed by expert evaluations. The module received a very high validity rating of 88% from instructional design experts and a high rating of 62% from content experts. Furthermore, the module was highly effective in improving teachers' skills, as evidenced by the positive feedback and high scores obtained from the teacher participants. The post-training survey revealed an average satisfaction rating of 93%, indicating a very high level of acceptance among the teachers.